Metafor Ne Değildir? - Şahan, Kayhan (My University, 2017)
Batı kaynaklı terminolojiden alınan “metafor”un, Türkçede geleneksel tasnif içine yerleştirilmesi ve kullanımında çeşitlilik oluşmuştur. Batıda, felsefe alanında temelleri atılan kavram, ülkemizde ise figüratif bir misyon yüklenerek mecaz, açıkkapalı istiare, ad aktarması, deyim aktarması, telmih gibi birçok terim yerine kullanılmış ve örneklendirilmiştir.Metafor için dilimizde birçok farklı tanım yapılmış olmasına rağmen henüz yeterince tartışılmamış ve yerine oturtulamamıştır. Buna rağmen Türkçede metafor; tezlere, makalelere kaynaklık eder bir hale gelmiştir. Tüm doğruları, yanlışları, tanımlamaları, örneklemeleri ve Türkçeleştirmeleri ile bu kaynaklar bütünü, bugün kavramın tanımlanabilmesi için öncelikle farklılıkların ayrıştırılması ve ayıklanması gereğini doğurmuşlardır. Bir başka deyişle metafor kavramı etrafında yapılan çok çeşitli isimlendirme, tanımlama ve örneklendirme deneyimleri “metafor ne değildir?” sorusunu beraberinde getirmiştir. Çalışma, bu soru çerçevesinde asıl sorunun cevabını aramaktadır.

“Metaphor” – borrowed from Western terminology – has been embedded and used within traditional classification in Turkish in diverse ways. Metaphor, of which foundation was set within the field of philosophy in the West, undertook a figurative mission in Turkish, and it is used and exemplified as a substitute for simile, open/closed figures of speech, metonymy, synecdoche, and referencing. Although various definitions have been made for metaphor in Turkish language, the concept of metaphor has not been fully discussed and established. However, metaphor has become a source for articles and dissertations written in Turkish. The combination of these sources - with all the rights and wrongs, descriptions, definitions, exemplifications, and Turkishifications - has generated a necessity to sort and distinguish the differences found among these sources to establish a common ground for the definition of the concept of metaphor. In other words, all the attempts that have been made to label, define and exemplify the concept of metaphor have brought along the question of “What is not metaphor?”. This study aims to provide answers for the main problem within the realm of this question.
What Methaphor is Not?
Keywords: Metafor; Söz Sanatları; Retorik; Metaphor; Figure of Speech; Rhetoric